The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/0969594x.2016.1244514
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ approaches to classroom assessment: a large-scale survey

Abstract: Classroom assessment has become a cornerstone of today's standards-based system of education. However, recent policy developments, professional standards, and variable assessment education have led to significant variability in teachers' approaches to assessment. The primary purpose of this research was to use a new instrument predicated on recently published classroom assessment standards-the Approaches to Classroom Assessment Inventory-to measure teachers' (a) approaches to assessment, (b) perceived skill in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 42 publications
5
38
0
1
Order By: Relevance
“…One of the essential purposes of assessment as learning is that students should become the protagonists of their learning (Coombs et al 2018;DeLuca et al 2016). This means tutors must assume more of a role as facilitator.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…One of the essential purposes of assessment as learning is that students should become the protagonists of their learning (Coombs et al 2018;DeLuca et al 2016). This means tutors must assume more of a role as facilitator.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Even though the "range of assessment practices in schools today spans from traditional test-based behaviouristic approaches to contemporary socio-constructivist assessment practices" ( [19], p. 4), teachers' assessment practices remain relatively limited. For instance, Cheah [20] studied Malaysian teachers' assessment practices and concluded that their skills and knowledge were relatively poor.…”
Section: Current Level Of Teachers' Assessment Practicesmentioning
confidence: 99%
“…One factor that may contribute to poor assessment practices by the teachers is their experiences of assessment when they were students or at the beginning of their teaching career [19]. That is, some teachers may value and implement out dated assessment approaches because they believe that it gives them valid results and can provide a strong evidence of the extent of student learning [23,24].…”
Section: Current Level Of Teachers' Assessment Practicesmentioning
confidence: 99%
See 2 more Smart Citations